Levetiracetam, Calcium Antagonism, and Bipolar Disorder. Issue 4 (August 2015) - Dubovsky, Steven L.; Daurignac, Elsa; Leonard, Kenneth E.; Serotte, Jordan C.
Abstract : Abstract: Hyperactive intracellular calcium ion (Ca 2+ ) signaling in peripheral cells has been a reliable finding in bipolar disorder. Some established mood stabilizing medications, such as lithium and carbamazepine, have been found to normalize elevated intracellular Ca 2+ concentrations ([Ca 2+ ]i ) in platelets and lymphocytes from bipolar disorder patients, and some medications the primary effect of which is to attenuate increased [Ca 2+ ]i have been reported to have mood stabilizing properties. Hyperactive intracellular Ca 2+ signaling has also been implicated in epilepsy, and some anticonvulsants have calcium antagonist properties. This study demonstrated that levetiracetam, an anticonvulsant that has been shown to block N and P/Q-type calcium channels in animal studies does not alter elevated [Ca 2+ ]i in blood platelets of patients with bipolar disorder. Review of published clinical trials revealed no controlled evidence of efficacy as a mood stabilizer. This study underscores the possibility that pharmacologic actions of a medication in animals and normal subjects may not necessarily predict its pharmacologic or clinical effects in actual patients. Effects of treatments on pathophysiology that is demonstrated in clinical subtypes may be more likely to predict effectiveness in those subtypes than choosing medications based on structural similarities to established treatments.